Comparative Study on the Inclusion of Trans Fat Information in Processed Food Packaging between Indonesia and Singapore - Az Zahra, Shabrina Najla; Sakti, Muthia (UNIVERSITAS PAKUAN, 2025)
Abstract Excessive consumption of trans fats can increase LDL and triglyceride levels and decrease HDL levels. Therefore, an instrument is needed to protect consumers when consuming processed foods by including information about trans fat content on processed food packaging. The main topic of this research examines the regulations regarding the inclusion of trans fat information on processed food packaging in Indonesia and Singapore and the government's responsibility to consumers to provide accurate information. The research methods applied are the normative juridical method with a legislative approach, a comparative approach, and a case approach. Library research was applied as a data collection technique. This study shows that regulations regarding the inclusion of trans fat information in Indonesia and Singapore already exist, but there are several differences regarding the limits of trans fat content that can be contained in food and provisions regarding sanctions. Therefore, Indonesia can immediately create regulations regarding sanctions for violations of the inclusion of trans fat information on processed food packaging and consider the implementation of front-of-pack labeling. Keywords : Trans fat, Indonesia, Singapore.